Strategi Guru Dalam Menanamkan Nilai-Nilai Pendidikan Multikultural Di Era Disrupsi Untuk Menumbuhkan Sikap Pluralisme Siswa MTs Mazroillah Lubuk Linggau - Refriana, Isna; Suhirman, Suhirman; Nurlaili, Nurlaili (Edification Journal : Pendidikan Agama Islam, 2024)
Islamic boarding school is a school environment that is quite diverse both in terms of region, language, ethnicity, culture, economic background and parental education. Therefore, this thesis aims to find out the teacher's strategy in cultivating students' pluralism attitudes in the era of disruption through multicultural education. This type of research uses descriptive qualitative research. The research subjects were the principal, several teachers, caregivers and students or MTs students at the Mazroillah Islamic Boarding School Lubuk Linggau. Data collection techniques by way of observation, interviews and documentation. The data validation technique uses triangulation. Data analysis techniques by means of data reduction, data presentation, and conclusions. The results of the study show that the teacher's strategy in cultivating an attitude of pluralism through multicultural education is in three ways. First, the strategy of organizing learning is that learning activities are organized in the form of lesson plans in learning forums in class and outside the classroom. Second, the learning delivery strategy is understanding student character, understanding student diversity, and choosing the right approach such as cooperative learning methods, group discussions, advice and habituation. Third, the learning management strategy is by arranging student seats, realizing lesson plans by considering various factors such as student conditions, study time, facilities, environment and others. Furthermore, the supporting factors come from the Islamic boarding school climate, Islamic boarding school activities, extracurricular activities, and parents of students. The inhibiting factors are derived from students' innate attitudes, environment, and learning facilities. The solution to the inhibiting factors is through a special approach to students and parents and by using a variety of learning methods and utilizing existing learning media.